ELECTROCHEMICAL CHARACTERIZATION OF TWO OLEAMIDE ANALOGUES ANTI-OBESITY AGENTS - NEGUŢ (CIOATEŞ), Cătălina; UNGUREANU, Eleonora-Mihaela; ARNOLD, Georgiana-Luiza; TĂNASE, Constantin; BÎRZAN, Liviu (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Electrochemical characterization of two oleamide analogues was performed by cyclic voltammetry, differential pulse voltammetry, and rotating disk electrode voltammetry. Modified electrodes have been obtained by scanning the potential in the domain of the first oxidation peaks.